Physical Activity and Risk of Diagnosed and Undiagnosed Prediabetes among Males and Females in the National Health and Nutrition Examination Survey, 2007-2014 - Mabeline Velez; Lisa Chasan-Taber; Eva Goldwater; Nicole VanKim (Journal of Diabetes Research)
Aims. The purpose of the study was to assess the effect of leisure and occupational physical activity on the risk of diagnosed and undiagnosed prediabetes among females and males. Methods. A sample of 17,871 non-pregnant adults was drawn from the 2007-2014 National Health and Nutrition Examination Survey. Multinomial logistic regression tested associations between moderate-to-vigorous physical activity (MVPA) and risk of diagnosed prediabetes and undiagnosed prediabetes, compared to no prediabetes. Results. Females and males who met guidelines for total MVPA (i.e., ≥10 MET-hrs/week) had a statistically significant lower risk of undiagnosed prediabetes (OR range: 0.50-0.65) as compared to those with no MVPA, however findings were no longer statistically significant after adjustment for diabetes risk factors. In terms of diagnosed prediabetes, females meeting guidelines had lower risk (OR range: 0.65-0.76), while only males engaging in the most MVPA had lower risk; findings were no longer significant after adjustment. Patterns were similar for leisure-time MVPA, but conflicting for occupational PA; females with 10-20 MET-hrs/week had a higher risk of diagnosed prediabetes (OR =1.71, 95% CI 1.11-2.61) and males with >20 MET-hrs/week had a higher risk for undiagnosed prediabetes (OR =1.17, 95% CI 1.02-1.35) after adjustment. Conclusions. This study adds to the sparse body of literature on physical activity and prediabetes, particularly with its inclusion of occupational MVPA.